Carissa spinarum L. (Apocynaceae): A new addition to the fl ora of Nepal - Khatri, S.; Kurmi, P. P.; Bhatt, G. D. (Banko Janakari, 2013)
The genus Carissa L. consists about 30 species distributed in the tropics and subtropics of Africa, Asia and Australia (Shu, 1995). Five species are reported from India, four from China and two from Bhutan (Hooker, 1882; Shu, 1995 and Watson, 1999). In Nepal, Carissa represent one species namely Carissa carandus L. (Chater, 1982; Joshi, 1997; Press et al., 2000 and Bista et al., 2001). Carissa spinarum L. has been so far not reported from Nepal. This herbarium specimens was collected by Puran P. Kurmi from Udayapur at Udayapur Village Development Committee (VDC) of Kapilvastu district at an altitude of 150m. It has been identifi ed as Carissa spinarum L. and therefore, it is found to be a new addition to the fl ora of Nepal. This species is distinguished from the others by its secondary veins conspicuous on adaxial leaf surface; branches and abaxial leaf surface puberulent. DOI: http://dx.doi.org/10.3126/banko.v21i2.9144 Banko Janakari Vol. 21, No. 2, 2011 Page: 55-56 Uploaded date: November 11, 2013